2018
DOI: 10.1111/spc3.12380
|View full text |Cite
|
Sign up to set email alerts
|

Visual attention to members of own and other groups: Preferences, determinants, and consequences

Abstract: Many current and past theories of social categorization acknowledge and even underline the critical role that visual processing plays in intergroup misperceptions and biases, yet research that directly measures or manipulates these processes is limited. In the present paper, we reviewed the current literature on visual attention to own and other group faces. First, we explored the development of preferential attention in face processing. Next, we examined these processes in adults and show different patterns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 148 publications
1
22
0
Order By: Relevance
“…A recently growing number of studies have employed eye-tracking methodology to investigate if and how eye movements differ for ingroup versus outgroup faces, in order to better understand the underlying mechanism of the ORE (see also Kawakami, Friesen, & Vingilis-Jaremko, 2018, for a recent review). Eyetracking offers a straightforward approach to investigating processing differences of ingroup and outgroup faces, using fixations (i.e., states when the eyes remain fixated over a period of time) to derive a person's current focus of overt visual attention (Deubel & Schneider, 1996;Hoffman & Subramaniam, 1995).…”
Section: Eye-tracking the Other-race Effectmentioning
confidence: 99%
“…A recently growing number of studies have employed eye-tracking methodology to investigate if and how eye movements differ for ingroup versus outgroup faces, in order to better understand the underlying mechanism of the ORE (see also Kawakami, Friesen, & Vingilis-Jaremko, 2018, for a recent review). Eyetracking offers a straightforward approach to investigating processing differences of ingroup and outgroup faces, using fixations (i.e., states when the eyes remain fixated over a period of time) to derive a person's current focus of overt visual attention (Deubel & Schneider, 1996;Hoffman & Subramaniam, 1995).…”
Section: Eye-tracking the Other-race Effectmentioning
confidence: 99%
“…The authors suggested that one reason older children were more likely to avoid the use of race is because they wanted to escape the negative social consequences associated with appearing biased. Although a large literature has provided evidence that children attend to race from an early age, research has also demonstrated that racial color blindness increases as children learn social norms and are better able to regulate their behavior according to social expectations (Aboud, 2003;Anzures, Quinn, Pascalis, Slater, & Lee, 2010; for reviews see Kawakami, Friesen, & Vingilis-Jaremko, 2018;Kawakami, Hugenberg, & Dunham, 2019).…”
Section: Strategic Racial Color Blindnessmentioning
confidence: 99%
“…Individuals tend to process racial ingroup and outgroup members differently and these differences have important implications for intergroup relations (Marcon et al, 2010; DeGutis et al, 2013; Hayward et al, 2013; Kawakami et al, 2014, 2018). For example, research shows that individuals tend to remember faces of their own race better than those of other races (i.e., own-race bias, cross-race effect) (for a review see Meissner and Brigham, 2001; Walker and Tanaka, 2003; Walker and Hewstone, 2006; Mondloch et al, 2010; Zhao et al, 2014; Wan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While a large body of research has examined memory biases for racial ingroups and outgroups, fewer research has focused on attention biases to these groups. Examining attention biases to racial ingroups and outgroups is important because it has been implicated as a contributing factor in phenomena such as the own-race bias and interaction intentions with outgroup members (Hills and Lewis, 2006; Hugenberg et al, 2010; Hills and Pake, 2013; Kawakami et al, 2014, 2018; Zhou et al, 2015a,b). Additionally, some research suggests that early attention biases to Black relative to White faces may reflect an early vigilance to Black individuals due to stereotypes associating Black people with danger or threat (Trawalter et al, 2008).…”
Section: Introductionmentioning
confidence: 99%